Consumer Acceptance of App Push Notifications: Systematic Review on the Influence of Frequency - Wohllebe, Atilla (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Using push notifications, companies can address their smartphone app users with advertising messages. Each of these notifications can mean added value for smartphone users in terms of content, but also disruption and interruption. It is therefore important for advertisers to understand how the frequency of message delivery influences consumer acceptance. The systematic review is based on the PRISMA method and initially identifies a total of 18,725 potentially relevant scientific papers. The 17 research articles included in the qualitative synthesis show that push notifications are suitable for encouraging users to use an app and establish new habits. App usage increases with frequency, with particularly active users tolerating higher frequencies. At the same time it is also shown that too high a frequency can be perceived as disturbing and users should therefore be given the opportunity to determine the frequency with which they receive notifications. A gap in research has been identified in particular in studies that look at real observed behaviour of app users instead of behaviour reported via questionnaires and examine the interaction of frequency, content and presentation of notifications.